2016
DOI: 10.1002/atr.1381
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between PARAMICS and VISSIM in estimating automated field‐measured traffic conflicts at signalized intersections

Abstract: SUMMARYThe main objective of this study is to investigate the relationship between field-measured conflicts and simulated conflicts estimated from microsimulation model (PARAMICS) using the surrogate safety assessment model. An urban signalized intersection was selected for analysis. Automated video-based computer vision techniques were used to identify field conflicts. The applicability of a two-step model calibration procedure applied to VISSIM in a recent study was investigated using PARAMICS. In the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 30 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…Although the two calibration steps improved the SSAM results, the first step is shown to have the most significant impact. This is similar to recent findings from previous studies (6,20,24).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Although the two calibration steps improved the SSAM results, the first step is shown to have the most significant impact. This is similar to recent findings from previous studies (6,20,24).…”
Section: Resultssupporting
confidence: 93%
“…Although high correlation values between simulated and field-observed conflicts was obtained in previous studies, systematic overestimation or underestimation of the real number of conflicts was also found. Furthermore, major differences between simulated and field-observed conflicts in spatial distribution were detected (6,9,20,24). These discrepancies suggest that the high correlation between simulated and field-observed conflicts/crashes might come from the exposure dependency (i.e., both simulated and fieldobserved conflicts/crashes are correlated with traffic volume), not from the ability of simulation models to capture the real driving behavior and the actual conflict mechanism.…”
mentioning
confidence: 97%
“…Surrogate safety measures, such as time to collision (TTC), postencroachment time (PET), deceleration rate (DR), gap time (GT), and proportion of stopping distance (PSD), are useful measurements of the safety implications [30][31][32][33]. TTC, defined as the expected time for two vehicles to collide if they remain on the same path and at the same speed, is a widely used surrogate safety measure.…”
Section: Surrogate Safety Measuresmentioning
confidence: 99%
“…Essa and Sayed [25] performed a comparative analysis of the PARAMICS and VISSIM microsimulation models. The numerical experiments showed that the default model parameters gave poor correlation with the field-measured data.…”
Section: Detailed Review Of the Collected Studiesmentioning
confidence: 99%